Common variants increase risk for congenital diaphragmatic hernia within the context of de novo variants - Qiao, Lu; Welch, Carrie L.; Hernan, Rebecca; Wynn, Julia; Krishnan, Usha S.; Zalieckas, Jill M.; Buchmiller, Terry; Khlevner, Julie; De, Aliva; Farkouh-Karoleski, Christiana; Wagner, Amy J.; Heydweiller, Andreas; et al. (The American journal of human genetics, 2024)
Congenital diaphragmatic hernia (CDH) is a severe congenital anomaly often accompanied by other structural anomalies and/or neurobehavioral manifestations. Rare de novo protein-coding variants and copy-number variations contribute to CDH in the population. However, most individuals with CDH remain genetically undiagnosed. Here, we perform integrated de novo and common-variant analyses using 1,469 CDH individuals, including 1,064 child-parent trios and 6,133 ancestry-matched, unaffected controls for the genome-wide association study. We identify candidate CDH variants in 15 genes, including eight novel genes, through deleterious de novo variants. We further identify two genomic loci contributing to CDH risk through common variants with similar effect sizes among Europeans and Latinx. Both loci are in putative transcriptional regulatory regions of developmental patterning genes. Estimated heritability in common variants is ∼19%. Strikingly, there is no significant difference in estimated polygenic risk scores between isolated and complex CDH or between individuals harboring deleterious de novo variants and individuals without these variants. The data support a polygenic model as part of the CDH genetic architecture.